The effect of halal tour, word of mouth, price and social media on visiting decisions to non muslim countries at pt.tour and travel antavaya palembang - Desfika Rusmalita Utami; Misniwati Misniwati; Aryanti Aryanti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This study aims to determine the effect of the halal tour, word of mouth, price and social media on visiting decisions to non-muslim countries at PT.Tour and Antavaya Travel Palembang. The source of data is primary data through questionnaire. The sample of this study was 110 respondents, technique with purposive sampling method. This research used quantitative methods. with the multiple regression analysis method. The research variables consist of independent variables : 1.Halal Tour, 2.Word of mouth 3.Price 4.Social Media. While the dependent variable is the decision to visit. The result showed a halal tour didn’t significantly influence the visiting decision. Word of mouth, price, and social media are significantly influence on visiting decision.